Secure migration of WebAssembly-based mobile agents between secure enclaves - Pop, Bogdan (My University, 2021)
Cryptography and security protocols are today commonly used to protect data at-rest and in-transit. In contrast, protecting data in-use has seen only limited adoption. Secure data transfer methods employed today rarely provide guarantees regarding the trustworthiness of the software and hardware at the communication endpoints. The field of study that addresses these issues is called Trusted or Confidential Computing and relies on the use of hardware-based techniques. These techniques aim to isolate critical data and its processing from the rest of the system. More specifically, it investigates the use of hardware isolated Secure Execution Environments (SEEs) where applications cannot be tampered with during operation. Over the past few decades, several implementations of SEEs have been introduced, each based on a different hardware architecture. However, lately, the trend is to move towards architecture-independent SEEs. As part of this, Huawei research project is developing a secure enclave framework that enables secure execution and migration of applications (mobile agents), regardless of the underlying architecture. This thesis contributes to the development of the framework by participating in the design and implementation of a secure migration scheme for the mobile agents. The goal is a scheme wherein it is possible to transfer the mobile agent without compromising the security guarantees provided by SEEs. Further, the thesis also provides performance measurements of the migration scheme implemented in a proof of concept of the framework.
Keywords: Trusted Computing, Secure Enclaves, Secure Migration, Trusted channel, Mobile Agents